Gene expression profiling in patients with severe sepsis - Grealy, Christopher Robert (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Surgery, 2014)
The human response to infection ranges from mild illness which is relatively well tolerated to a severe, potentially life-threatening syndrome termed severe sepsis. This thesis explored this response in patients hospitalised patients with mild or non-septic infection and severe sepsis. Distinct patterns of particular cytokine mRNA levels were observed in circulating peripheral blood mononuclear cells from patients admitted to intensive care with severe sepsis compared to patients with non-septic infection not requiring intensive care. A means to quantify the degree of immune dysfunction through these assays is put forward. The basis of these changes in cytokine mRNA levels is investigated through ex vivo mechanistic studies. Genome wide transcriptional changes are evaluated in two populations of circulating mononuclear cells, namely the CD14* monocyte and the CD4+ lymphocyte.
Keywords: Surgery, Ph.D.; Ph.D. Trinity College Dublin